2022
DOI: 10.1186/s12889-022-14391-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance is associated with mild cognitive impairment: a community population-based cross-sectional study

Abstract: Background Sleep is conducive to the elimination of brain metabolites and the recovery of brain function. However, the relationship between sleep disturbance and Mild Cognitive Impairment is not fully been determined. Methods This was a community population-based cross-sectional study. A total of 1,443 participants from a village in the suburbs of Xi’an, China were enrolled in 2017. Sleep quality was evaluated using the Pittsburgh sleep quality ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…There appears to be a synergistic relationship between sleepdisordered breathing and Alzheimer's disease because they share certain etiological and physiopathological determinants that predispose them to the development of both disorders in the same patient (Figure 2) [34,82]. First, the presence of OSA, sleep fragmentation, and nocturnal hypoxia are linked with higher cognitive impairments such as decreased memory, attention, and executive function [83][84][85][86], symptoms inherent in AD. Furthermore, it was found that the more severe the form of OSA, the stronger the association between the apnea-hypopnea index, the oxygen desaturation index, and the prediction of memory impairment [87].…”
Section: Bidirectional Relationship Between Obstructive Sleep Apnea A...mentioning
confidence: 99%
“…There appears to be a synergistic relationship between sleepdisordered breathing and Alzheimer's disease because they share certain etiological and physiopathological determinants that predispose them to the development of both disorders in the same patient (Figure 2) [34,82]. First, the presence of OSA, sleep fragmentation, and nocturnal hypoxia are linked with higher cognitive impairments such as decreased memory, attention, and executive function [83][84][85][86], symptoms inherent in AD. Furthermore, it was found that the more severe the form of OSA, the stronger the association between the apnea-hypopnea index, the oxygen desaturation index, and the prediction of memory impairment [87].…”
Section: Bidirectional Relationship Between Obstructive Sleep Apnea A...mentioning
confidence: 99%
“…Prior work has shown that self-reported sleep quality is associated with cognitive decline, in particular executive function [20]. Three recent cross-sectional studies have also linked poor sleep quality to various neurological outcomes, including lower global cognition scores [21], lower cerebrospinal fluid (CSF) Aβ42 levels [21], higher CSF total tau levels [21], higher likelihood of having MCI [22], and more subjective cognitive complaints [23]. An analysis of 1168 older adults without dementia within the EPAD dataset found that self-reported poor sleep quality was linked to higher levels of CSF t-tau [24 ▪▪ ], cross-sectionally.…”
Section: Sleep Qualitymentioning
confidence: 99%
“…[9] In fact, research has shown that listening to and playing music can change brain functions, improving cognitive functions such as memory [10] and attention, [11] as well as behavioral symptoms of older adults. [12] Long-term music training and learning of related skills can even stimulate the brain development of older adults. [13] Music intervention has also been shown to alleviate negative emotions such as anxiety [14] and depression, [15] and activate the subcortical circuit, limbic system, and emotional reward system, thereby stimulating well-being and improving the quality of life.…”
Section: Databasesmentioning
confidence: 99%